In vivo Models of Chemically Induced Colitis for Inflammatory Bowel Diseases: An Overview - Jaiswal, Meenakshi; Agrawal, Nidhi; Kumar, Yogendra; Lanjhiyana, S. K. (Challenges and Advances in Pharmaceutical Research Vol. 10, 2022)
The most common chronic gastrointestinal condition in children and adolescents is Inflammatory Bowel Disease (IBD). IBD is a group of reoccurring and remitting inflammatory gastrointestinal diseases, the most common of which are ulcerative colitis (UC) and Crohn's disease (CD). IBD is a complex disruption of intestinal immune homeostasis characterized by changes in intestinal barrier permeability and an abnormal immunological response to luminal microflora. Several animal models of IBD have been established over the last 2-3 decades, assisting in the identification of novel therapeutic targets and medication treatments, as well as defining a mechanism for abortive and preventative medications. These animal models have provided relevant knowledge as well as a framework for considering the effects of hormones, genes, and numerous environmental stimuli such as sound, light, etc. on the pathophysiology of IBD. This chapter aims to present the most popular chemically induced models of intestinal inflammation for the assessment of new drugs. Each model outlined specific pathological characteristics of IBD, such as chronic inflammation, mucosal layer disruption, increased gut permeability, etc. In addition to several IBD animal models, this study addressed the histological features of the disease-related conditions.